Gender stereotyping and wage discrimination among Italian graduates - Carolina Castagnetti; Luisa Rosti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
This paper addresses the gender pay gap among Italian university graduates on entry to the labour market and stresses the importance of gender stereotypes on subjective assessment of individual productivity. Our data show that in contexts where the stereotype is most likely to occur, the unexplained component of the gender pay gap is higher. Moreover, we find evidence that being excellent at school does not ensures that a woman will be rewarded as an equivalently performing man, but serves to counteract the gender bias in on-the-job evaluations.
Keywords: 330; Lohnstruktur; Fraueneinkommen; Arbeitsmarktdiskriminierung; Akademiker; Italien